Clinical characteristics and COVID-19 outcomes in a regional cohort of pediatric patients with rheumatic diseases - Daniel Clemente (BMC, 2021)
Abstract Background This study aimed to assess the baseline characteristics and clinical outcomes of coronavirus disease 2019 (COVID-19) in pediatric patients with rheumatic and musculoskeletal diseases (RMD) and identify the risk factors associated with symptomatic or severe disease defined as hospital admission, intensive care admission or death. Methods An observational longitudinal study was conducted during the first year of the SARS-CoV-2 pandemic (March 2020–March 2021). All pediatric patients attended at the rheumatology outpatient clinics of six tertiary referral hospitals in Madrid, Spain, with a diagnosis of RMD and COVID-19 were included. Main outcomes were symptomatic disease and hospital admission. The covariates were sociodemographic and clinical characteristics and treatment regimens. We ran a multivariable logistic regression model to assess associated factors for outcomes. Results The study population included 77 pediatric patients. Mean age was 11.88 (4.04) years Of these, 30 patients (38.96%) were asymptomatic, 41 (53.25%) had a mild-moderate COVID-19 and 6 patients (7.79%) required hospital admission. The median length of hospital admission was 5 (2–20) days, one patient required intensive care and there were no deaths. Previous comorbidities increased the risk for symptomatic disease and hospital admission. Compared with outpatients, the factor independently associated with hospital admission was previous use of glucocorticoids (OR 3.51; p = 0.00). No statistically significant risk factors for symptomatic COVID-19 were found in the final model. Conclusion No differences in COVID-19 outcomes according to childhood-onset rheumatic disease types were found. Results suggest that associated comorbidities and treatment with glucocorticoids increase the risk of hospital admission.